?Effect of Dehydration on Storage Stability of Two Varieties of Jamun Fruit: ?Short Communication (Biological Sciences - PJSIR, 1994)
Jamun fruit (Eugenia jambolana L.) belongs to family Myrtaceae and thrives well in Pakistan. Being a highly perish- able fruit, it was, therefore, planned to preserve the available two varieties of Jamun by dehydration and to assess the changes in quality during extended period of storage.